Household Solid Waste Management and Environmental Impacts in the Ibadan Metropolis, Nigeria - Ogunwale, Taiwo Olusegun; Oladeji, Peter B.; Oyedare, Adekunle Benjamin; Oyetola, Simeon Oyesoji; Oluwalana, Ayodeji Isaac; Basiru, Taofeek Adekola; Ogungbile, Peter O.; Balogun, Francis Adeniyi; Oduah, Oluwaseun Adewunmi; Ogunrinola, Oluwaseun Femi (Tecno Scientifica Publishing, 2024)
Given the current rate of urbanization, municipalities in most Nigerian cities have struggled with the collection, transportation, and disposal of solid waste. This is due to waste generation, both residential and commercial, occurring in a dispersed manner across homes, buildings, streets, parks, and even vacant spaces within communities. This manuscript aims to evaluate the state of municipal solid waste management in Ibadan, household solid waste storage practices, and the locations of solid waste storage containers (skip points) in relation to accessibility and health risks to the community, in accordance with Nigerian National Solid Waste Management Standards and other pertinent international standards. A structured questionnaire was distributed to 21 micro and small firms and 250 homes in each of the three local government areas of the metropolis, with descriptive statistics used to interpret the data. According to the study results, inadequate Municipal Solid Waste Management (MSWM) service delivery in the Ibadan metropolitan area can be attributed to several issues, including a lack of institutional coordination among urban planners. The study’s conclusions indicate that the state of MSWM in the sampled areas is either inadequate or has poor spatial coverage and container utilization. Lastly, the study primarily suggests that these measures can reduce problems associated with MSWM by encouraging public-private partnerships, fostering effective institutional coordination with urban planner consultants in MSWM and skip-point location, and motivating the community to adopt integrated sustainable Solid Waste Management (SWM) strategies.